Advancements in reactor design, radiation safety, and radiation exposure management in Indian pressurized heavy water reactors - Veerendra Danannavar; U. K. Jayaram; G. K. Sunil; R. G. Pathak; B. Vinodkumar; N. Karunakara (Radiation Protection and Environment)
Nuclear Power Corporation of India Limited operates indigenously designed and constructed pressurized heavy water reactors (PHWRs) to harness nuclear energy and cater to the country’s energy needs. At present, the installed capacity of PHWRs in India is 6460 MWe. Occupational radiation workers may be exposed to radioactive fission products, coolant activation products, and activated corrosion products during reactor operation and maintenance. The radiation doses to the occupational radiation workers are meticulously monitored and the effective (E) dose and equivalent doses (HT) records are maintained. The dose limits for occupational workers are prescribed by the Atomic Energy Regulatory Board (AERB) in line with International Commission on Radiological Protection (ICRP). Over the years of PHWR operation, many improvements in design have been incorporated, and radiation safety practices have been developed. This article reviews the reactor design improvements, radiation safety practices, and radiation exposure management in Indian PHWRs. A comparative study of collective dose (CD) consumption of Indian PHWRs with world PHWRs is conducted. The study indicated that the CD consumption per reactor per year of Indian PHWRs is lower than other PHWRs worldwide. In Indian PHWRs, design modifications, ALARA measures and good practices adopted, a holistic approach to address the important issues, and operating experience sharing have yielded promising results in reducing CD consumption. The CD consumption of Indian PHWRs has attained stability over the years. Among all the operating Indian PHWRs, the Kaiga Generating Station (reactor units 3 and 4, each of 220 MWe) has achieved excellence in achieving lower CD consumption.